Machine learning techniques for predicting the quantity of ANFO used in blasting a bench in an open pit mine - Quispe-Tello, Rosa Liliam (2024)
The objective of this study is to predict the quantity of ANFO required for bench blasting in an open pit mine in Peru, through the application of advanced machine learning techniques. Six models were selected: Artificial Neural Networks (ANNMLP), Random Forests (RF), Support Vector Machines for Regression (SVR), Extreme Gradient Boosting (XGBoost), K-Nearest Neighbors (KNN), and Bayesian Regression (BR), due to their ability to handle complex multidimensional data and their success in similar applications, such as rock fragmentation prediction. The methodology included the collection of data from 208 drill holes, which were divided into training (70%), validation (15%), and testing (15%) sets. The models were evaluated using RMSE, MSE, MAE, and R2. The KNN model showed the best performance, with an R2 of 0.84, RMSE of 2.37, MSE of 5.60, and MAE of 1.35, standing out in predictive accuracy. This study contributes to the accurate prediction of the ANFO quantity required for bench blasting in open-pit mining, providing a useful tool for improving explosives management based on the specific characteristics of the terrain and operational conditions.